Donor characteristics and hematopoietic stem cell transplantation outcome : experience of a single center in Southern Brazil - Paz, Alessandra Aparecida (2018)
Background: Hematopoietic stem cell transplantation is a curative treatment for many patients with hematological disorders. Donor–recipient genetic disparity, especially involving the human leukocyte antigen system is a critical factor for transplant outcome. Objective: To evaluate retrospectively donor characteristics and correlations with the occurrence of acute and chronic graft-versus-host disease, disease-free survival and overall survival in a Brazilian population submitted to allogeneic hematopoietic stem cell transplantation between 1994 and 2012 in a single center. Results: Three hundred and forty-seven consecutive transplantations were included. Related transplants (81.2%) were significantly more common than unrelated transplants (18.7%); donor and recipient median ages were 34 (range: 1–61) and 33 (range: 3–65) years respectively with donor HLAs being matched for 333 (95.9%) patients. Donor gender, cytomegalovirus status and ABO incompatibility did not influence the five-year overall survival. In univariate analyses, overall survival was negatively influenced by the presence of acute graft-versus-host disease (33% vs. 47%, respectively; p-value = 0.04), unrelated transplant (41.5% vs. 50.9%, respectively; p-value = 0.045) and donors aged over 40 years (41% vs. 52%, respectively; p-value = 0.03). Older donors were associated with a higher rate of acute (52% vs. 65.8%; p-value = 0.03) and chronic graft-versus-host disease (60% vs. 43%, respectively; p-value = 0.015). In multivariate analyses, acute graft-versus-host disease [relative risk (RR): 1.8; 95% confidence interval (CI): 1.1–29; p-value = 0.008] and older donors (RR: 1.6; 95% CI 1.11–2.24; p-value = 0.013) were associated with higher transplant-related mortality. Conclusions: In transplant patients, to have a donor older than 40 years of age seems to significantly increase the incidence of acute and chronic graft-versus-host disease and transplant-related mortality with no impact on disease-free survival and overall survival. In spite of the rather small cohort of patients, these findings are similar to what is described in the literature suggesting that a younger donor should be chosen whenever possible.